Landscape effects of conflicts in space management. A historical approach based on the Silesian and Żywiec Beskids (West Carpathians, Poland) - Sobala Michał (Environmental & Socio-economic Studies, 2016)
A land use regime undergoes much change over time depending on the growth in the importance of various interest groups. Spatial conflicts repeatedly accompany this growth. The aim of the article is to determine the relationship between spatial conflicts and landscape changes. On the basis of the Silesian and Żywiec Beskid mountain ranges, it has been proven that conflicts arising between mountain grazing, agriculture, forest management, contemporary building and tourism development have significant impacts on the landscape. To this end, archive and contemporary cartographic materials, historical scientific works and archive photographs were used. The conflicts between mountain grazing and other types of human activity in the study area were analysed. Subsequently, their influence on the landscape was determined. As a result of the study, the primary sources of conflicts were indicated and correlated with historical periods and the predominant landscape use regime. The imprints of historical space conflicts and the rivalry for land use between different entities for their own purposes are still visible in the landscape. The historical conflicts have arisen between entities seeking ways to use different environmental resources occurring in the same area. Contemporary conflicts arise between entities seeking ways to use environmental resources (tourism) and between entities conscious of the hazards of the landscape sustainability resulting from the utilization of environmental resources (nature conservation services). Both historical and contemporary conflicts usually have a violent course resulting from the lack, or deficiency of, legislation concerning land management.